The weak turbulence methods in the problem of galaxy mass distribution function - Kontorovich, V.M. (Вопросы атомной науки и техники, 2000)
The analogy between the turbulent Kolmogorov type spectra and the distribution of galaxies on masses is discussed. Due to nonlocality [1] of galaxy mass spectrum formed by merging the additional approximate conservation law affects its intermediate asymptotics power index, which proves to be intervening between the constant mass flux and this of the number of massive galaxies. Analytical description of this asymptotics, which essentially uses the Smoluchowsky kinetic equation symmetry transformation, is presented. The result is compared with the recently discovered steepness of galaxy luminosity function on its faint edge. The problem of the main part of barionic mass in the Universe is shortly discussed in this context.